Comparison of clinical manifestations, pre-existing comorbidities, complications and treatment modalities in severe and non-severe COVID-19 patients: A systemic review and meta-analysis - Giri, Mohan (Sci Prog, 2021)
The global pandemic of novel coronavirus disease 2019 (COVID-19) has become an emergency of major international concern. We aim to assess the prevalence of clinical manifestations, pre-existing comorbidities, complications and treatment modalities in COVID-19 patients and compare incidence of these clinical data of severe patients with non-severe patients. An electronic search was performed in four databases to identify studies reporting clinical data of severe and non-severe COVID-19 patients. We calculated the odds ratio (OR) using fixed or random effect model. The analysis included 41 studies with 16,495 patients. The most prevalent clinical manifestations were fever 78.1%, cough 64.6%, fatigue 40.8%, and dyspnea 38.6%. Dyspnea (OR: 4.20, 95% CI: 3.09–5.72), cough (OR: 1.45, 95% CI: 1.18–1.78), and fatigue (OR: 1.40, 95% CI: 1.14–1.72) were found to be statistically significant higher in severe COVID-19 patients. We found that the most prevalent comorbidities were hypertension 32.2%, diabetes 17.1%, and cardiovascular disease 15.3%. Compared with non-severe group, proportion of hypertension (OR: 1.98, 95% CI: 1.62–2.42), diabetes (OR: 2.04, 95% CI: 1.67–2.50), cardiovascular disease (OR: 2.78, 95% CI: 2.00–3.86), and cancer (OR: 1.75, 95% CI: 1.40–2.18) were statistically significant higher in severe group. 24.7% patients presented with ARDS. The pooled effect of ARDS in severe and non-severe cases was 42.69 (OR: 42.69, 95% CI: 21.62–84.31). There was significant higher incidence of antiviral drugs, antibiotics, and glucocorticoids use in severe patients. Compared with non-severe patients, symptoms such as fever, cough, dyspnea, existing comorbidities, and complications are prevalent in severe COVID-19 patients.